The Counselor in the schools : A Reconceptualization - Boy, Angelo V.; Pine, Gerald J. (Boston, Massachusetts : Houghton Mifflin Company, 1968)
School counseling has made many advances in the past decade but it has some distance to travel before the school counselor can legitimately be called a professional. There is convincing evidence that the majority of school counselors still conceptualize themselves as pupil prodders, loose-end coordinators, assistant administrators, and wooden task performers.
1. His Integration of educational and counseling goals -- 2. His sensitivity to the valuing process -- 3. His role concept -- 4. His perception of youth -- 5. His sensitivity to theoretical implications -- 6. His concept and translation of personality theory -- 7. His concept of counseling -- 8. His separation of counseling and guidance -- 9. His perspective on the use of information in counseling -- 10. His awareness of group counseling -- 11. His Concept of evaluation -- 12. His concept of a substantive counseling program -- 13. His experience in counselor education -- 14. Karen -- 15. Joe.
Includes index.
Keywords: COUNSELING